ИЗВРШУВАЊЕ НА МЕРКАТА ПРИТВОР ВО ПРИТВОРСКИТЕ ОДДЕЛЕНИЈА НА ЗАТВОРИТЕ ВО РЕПУБЛИКА МАКЕДОНИЈА: ПОЛОЖБАТА НА ПРИТВОРЕНИТЕ ЛИЦА ВО РЕПУБЛИКА МАКЕДОНИЈА DE JUREИ DE FACTO - Gruevska Drakulevski, Aleksandra (My University, 2015)
In this article the author analysis the characteristics of the penitentiary system in the Republic of Macedonia and the position of the detainees de jure and de facto. The author concludes that the penitentiary system in our country has the features of a modern system. He is one of the penitentiary systems that fully incorporate the Standard Minimum Rules for the Treatment of Prisoners and the European Prison Rules in the Law on Execution of Sanctions. The paper provides an overview of the international and the national regulations on the execution of detention, and also, it provides an analysis of the situation of the detainees in the country. The author specifically analyses the acute problems facing the penitentiary system regarding the enforcement of the detention and the situation of the detainees de jure and de facto and mechanisms to protect the rights of detainees. Although data on the execution of detention in the country are scarce, the author of the paper analyses the detention using data from the reports of the Committee of the Council of Europe for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment (CPT) and the National Preventive Mechanism (NPM) under the Ombudsman, as well as annual reports of the Directorate for Execution of Sanctions on the condition and operation of the penal and correctional institutions in the country. From the analysis of the reports the general conclusion is that regardless of the fact that the rights of the detainees are guaranteed by the law and by the international documents and must not be violated and they also determine obligations whose execution does not degrade the personality of the detainees, however, in practice there is a discrepancy between the situation of detainees, de jure and de facto. The author of the paper detects key problems facing our penitentiary system in terms of the execution of detention, namely: overcrowding (overcrowding) in the detention units in the prisons; substandard conditions in detention units in prisons, inadequate arrangements for detainees, improper treatment of detainees by prison staff, inadequate nutrition, inadequate health care of detainees, inadequate staffing of detention departments, etc.
THE EXECUTION OF DETENTION IN THE DETENTION DEPARTMENTS OF PRISONS IN THE REPUBLIC OF MACEDONIA: THE POSITION OF DETAINED PERSONS IN MACEDONIA DE JURE AND DE FACTO
Keywords: penitentiary system, detainees, position of detainees, detention.